Is Muslim Tourist Satisfaction in Muslim Destination and Non-Muslim Destination Different? - Anthony Brien; Izyanti Awang Razli; Widi Senalasari; Tjetjep Djatnika; Tintin Suhaeni (Politeknik Negeri Bandung, 2022)
This study is intended to assess Muslim tourist satisfaction across Muslim and non-Muslim destinations, seeing from the attractions, halal, and people's experiences. It also observes religiosity’s role in the link between tourist experience and satisfaction in both tourism destinations. Data was obtained from surveying 479 Muslim tourists in Indonesia and 270 in Taiwan and analyzed using partial least squares techniques. The results indicate that the tourist experience is an essential driver of Muslim tourist satisfaction in Indonesia and Taiwan. While experience with halal products and services is an essential driver for tourists visiting Muslim destinations, the case does not occur for tourists visiting non-Muslim destinations. Next, although religiosity significantly impacts the halal experience, it does not moderate the relationship between halal experience, tourist satisfaction, and tourism attraction experience. The findings suggest tourism marketers and attraction managers in both Muslim and non-Muslim destinations increase their focus on enhancing the attraction experience. Further, to strengthen tourist attractions’ attractiveness, special attention should be given to the availability of halal products, which impacts the acceptance of this important cultural element by locals and tourists.